Effect of some antioxidants on the prostate of adult and aged albino rats: a histological and immunohistochemical study - Mohamed Sayed Gabry, Dina Helmy Abdel Kader*, Maiada Moustafa, Asmaa Abdel Hamed Elenany (Journal of Applied Pharmaceutical Science, 2014)
Effect of some antioxidants on the prostate of adult and aged albino rats. Twenty-five adult and twenty-five aged male albino rats were divided into four groups: group I (control group) group II (zinc sulphate treated group), group III (vitamin E) & group IV (vitamin C) zinc administered in doses of 0.2673 mg for adult rat and 0.693 mg for aged rat, vitamin E administered in doses of 0.973 mg for adult rat and 2.52 mg for aged rat, vitamin C administered in doses of 1.215mg for adult rat and 3.15 mg for aged rat. The prostate glands were processed and stained by H&E, Masson trichrome & immunoreaction of androgen receptor for light microscopic examinations. Morphometric analysis for collagen fibers and immunoreaction area percent was performed and statically analyzed. Zinc showed improvements, in which decrease in number of mucosal fold and increase in immunoreactions of nuclear androgen receptor in ventral lobe also, Decrease fibrosis and increase in immunoreactions of nuclear androgen receptor in dorsolateral lobe. vitamin E showed improvements, in which decrease in number of mucosal fold, decrease size of acini, decrease of epithelial heights and increase in immunoreactions of nuclear androgen receptor in ventral lobe also, decrease of epithelial heights, decrease fibrosis and increase in immunoreactions of nuclear androgen receptor in dorsolateral lobe. vitamin C there were improvements, in which decrease in number of mucosal fold, dilatation of acini and slightly increase in immunoreactions of nuclear androgen receptor in ventral lobe also, rarified collagenous fibers and increase in immunoreactions of nuclear androgen receptor in dorsolateral lobe. It also ameliorated blood vessels congestion. Zinc, vitamin E and vitamin C exerted no harmful effects on adult prostate but ameliorated effects against aged prostate.
Keywords: Aging, prostate, zinc, vitamin E, vitamin C, prostatic hypertrophy, Rat.